Material requirements planning application: a case study of dinning table furniture manufacturer - Mohd Nor, Norasmiha; Rahman, Muhammad Syahmi; Mohd Lazim, Nur Azlin; Mohamad Rasul, Nur Hadirah Razi; Abdullah, Nor Fadilah; Rama Rao, Kavita Sai; Cheam, Kai Wen (Penerbit UTHM, 2020)
A company or industry will use production planning as a method to manufacture and to plan production modules. Resource such as employee, material and the capacity of production was fully utilize and to serve or give service to different customers (Juneja, 2020). The major problem such as inventory management, the utilization of resources and low productivities will address clearly in Production Planning and control. The efficiency or the effectiveness of an organization can calculated by checking its economical operation and to build and integrate the system of production planning and control (Geršak, 2013). There are 4 factors that encompass a production system: quality, quantity, time and cost. By analyzing the data, a well plan of production planning can be created which includes the data such as the demand volume of products, delivery schedule etc.